Synthesis and biological evaluation of some novel 1-indanone thiazolylhydrazone derivatives as anti-Trypanosoma cruzi agents - Caputto, Maria Eugenia (2012)
A series of novel 4-arylthiazolylhydrazones (TZHs) derived from 1-indanones were synthesized in good yields (66-92%) in a simple procedure using microwave irradiation and then characterized by spectroscopy studies. The compounds were evaluated for their in vitro anti-Trypanosoma cruzi activity against the epimastigote, trypomastigote and amastigote forms of the parasite. Most TZHs displayed excellent activity, and were more potent and selective than the reference drug Benznidazole, used in the current chemotherapy. Analysis of the free sterols from parasite incubated with the compounds showed that inhibition of ergosterol biosynthesis is a possible target for the action of these new TZHs. In particular, TZH 9 emerged as a promising antichagasic compound to be evaluated in animal models.